2018
DOI: 10.1097/md.0000000000012768
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study of MR mTI-ASL and DSC-PWI in evaluating cerebral hemodynamics of patients with Moyamoya disease

Abstract: The aim of this study was to explore the correlation between multi-inversion time arterial spin labeling (mTI-ASL) and dynamic susceptibility contrast-enhanced perfusion weighted imaging (DSC-PWI) in assessment of hemodynamics of patients with Moyamoya disease (MMD).In this study, 24 MMD patients and 21 healthy subjects were enrolled between June 2017 and December 2017. The images of mTI-ASL and DSC-PWI in the week before revascularization surgery were retrospectively analyzed. The parameters of cerebral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Other studies have compared ASL to perfusion MRI. For example, Zhang et al 48 retrospectively explored the correlation between multi-inversion time ASL (mTI-ASL) and DSC-PWI in 24 patients with MMD. As in the study by Ha et al, 13 relative perfusion values were attained by dividing by the cerebellum value, for both ASL-and DSC-acquired images.…”
Section: Asl and Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have compared ASL to perfusion MRI. For example, Zhang et al 48 retrospectively explored the correlation between multi-inversion time ASL (mTI-ASL) and DSC-PWI in 24 patients with MMD. As in the study by Ha et al, 13 relative perfusion values were attained by dividing by the cerebellum value, for both ASL-and DSC-acquired images.…”
Section: Asl and Mrimentioning
confidence: 99%
“…Ultimately, their findings showed that mTI-ASL is a viable contrast-free alternative when assessing MMD preoperatively, with a strong correlation between relative CBF measured by ASL and that measured by DSC-PWI (r = 0.839, p < 0.001), using Pearson correlation analysis in all ROIs analyzed (total of 90 lateral MCA territories and basal ganglia). 48 Qiao et al 31 also compared mTI-ASL and DSC MRI in quantifying CBF before and after revascularization in 41 MMD patients. The results showed that CBF measured by ASL and relative CBF measured by DSC in 824 ROIs were significantly correlated (r = 0.316, p < 0.0001).…”
Section: Asl and Mrimentioning
confidence: 99%
“…Additionally, territory-specific perfusion measured by cerebral blood flow (CBF) imaging also plays a determine role in disease severity and whether to choose bypass surgery or not. Pseudocontinuous arterial spin labeling (pCASL) is a non-invasive MR perfusion imaging technique, which is a feasible way to access CBF changes in patients with MMD ( 11 , 12 ). pCASL with multiple postlabeling delay (PLD) could provide more accurate CBF measurements because of the severe intracranial arterial stenosis and occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Digital subtraction angiography (DSA) is the gold standard for diagnosis, but Magnetic Resonance Angiography (MRA) is also helpful [40,41]. More specific methods but not currently used because of the costs and equipment involved are xenon-enhanced CT, DSC, MRI, H 2 [ [15]O]-PET and [42]I aromatic amines SPECT [43][44][45][46][47][48]. These diagnostic techniques are used for preoperative evaluation to decide the best surgical approach.…”
Section: Introductionmentioning
confidence: 99%